Fatal Chryseobacterium indologenes infection in a captive red‐shanked Douc langur (Pygathrix nemaeus). Issue 4 (22nd March 2022) - Chong, Shin Min; Douay, Guillaume; Heng, Yirui; Chng, You Rong; Tay, Yih Hong; Wong, Wai Kwan
Abstract: We report a case of fatal Chryseobacterium indologenes infection in a captive juvenile red‐shanked Douc langur in Singapore Zoo. The animal was treated for suspected melioidosis but died within 48 h. Chryseobacterium indolegenes was isolated from the liver and should be included as a differential for bacterial infections in the tropics.